The road to conflict resolution: A comparative analysis of frozen conflicts in the OSCE area - Trapara Vladimir; Jončić Miloš (Međunarodni Problemi, 2012)
In this paper the authors comparatively analyze the frozen conflicts in the OSCE area with an objective to discover specific features of the road to their solution. An accent has been put on the post-Soviet conflicts, while Kosovo and Cyprus are treated as subsidiary cases. A decisive element of the frozen conflict definition is a disharmony between the legal and factual state regarding territorial changes which took place as a consequence of an armed conflict. Thus, the international law aspect is the most important in considering possibilities for settlement of these conflicts. Other aspects which are analyzed in the paper are security, energy, economic, and democratic ones. The common conclusion of the analysis of each of these aspects is that the USA and Russia are the key actors which influence these frozen conflicts’ resolution. In the absence of their consensus, these conflicts are doomed to remain frozen in the long run.